Immunomodulatory effect of pachymaran on cyclosporine A (CsA)-induced lung injury in mice - Chen Kaiqin; Wei Ke; Ye Chun; Zhao Tianhao; Zhang Bo; Xiao Rong; Lu Fangguo (KeAi Communications Co., Ltd., 2022)
Objective: To investigate the immunomodulatory effect of pachymaran on cyclosporine A (CsA)-induced lung injury in mice. Methods: (i) Fifty male BALB/c mice were randomly divided into five groups (10 mice in each group): normal control (NC) group, 30, 45, and 60 mg/kg CsA groups, and lipopolysaccharide (LPS) group. Except for the NC group, other groups underwent CsA modeling. The NC group was treated with phosphate-buffered saline (PBS), the LPS group with 10 mg/kg LPS eight hours before mice euthanized, and the 30, 45, and 60 mg/kg CsA groups with corresponding doses of CsA for seven consecutive days. After treatment, the body and organ mass of each group were weighed, and the lung, thymus, and spleen indexes were calculated. Hematoxylin-Eosin (HE) staining was performed to observe histopathological changes in the lungs of the mice. The protein expression levels of interleukin (IL)-2 and IL-1β in the blood were detected using enzyme-linked immunosorbent assay (ELISA), and those of surfactant protein D (SP-D), IL-2, and IL-6 in lung tissues were detected by immunohistochemistry (IHC). The mRNA expression levels of SP-D, IL-1β, IL-6, and myeloperoxidase (MPO) in the lung tissues were detected by quantitative reverse transcriptase-polymerase chain reaction (qRT-PCR). (ii) Another 60 BALB/c mice were divided into six groups (10 mice in each group) : NC group, model control (MC) group, 50, 100, and 200 mg/kg pachymaran groups, and polyinosinic-polycytidylic acid [poly(I:C)] group. Except for the NC group, other groups underwent 45 mg/kg CsA modeling. The NC and MC groups were treated with distilled water, the pachymaran groups with corresponding doses pachymaran, and the poly(I:C) group with 0.1 mg/kg poly(I:C) for seven days.The mice were euthanized to obtain tissues and serum for detection. Detection methods were identical to those described in (i) above. Results: (i) CsA (30 mg/kg) increased the lung index of mice (P < 0.001), and decreased the spleen index (P < 0.01), thymus index (P < 0.05), and the serum level of IL-2 (P < 0.05). CsA (45 mg/kg) decreased the spleen, thymus indexes, and the serum level of IL-2 (P < 0.01) in mice, and increased the serum level of IL-1β (P < 0.05) and the protein level of lung SP-D (P <0.001). CsA (60 mg/kg) increased the lung index of mice (P < 0.01), the serum level of IL-1β (P < 0.05), the protein level of lung SP-D (P < 0.01), and the mRNA levels of lung MPO and SP-D ( P < 0.05), and decreased the thymus index of mice (P < 0.01). HE staining showed that 30, 45, and 60 mg/kg CsA, and LPS caused pathological changes in the lung tissue of mice. (ii) After pachymaran intervention in MC mice, the spleen and thymus indexes (P < 0.05) were increased in the 100 and 200 mg/kg pachymaran groups, and the lung index was decreased (P < 0.05). Moreover, 50 mg/kg pachymaran increased the thymus index (P < 0.05) and decreased the lung index (P < 0.01) in MC group. Pachymaran (50, 100, and 200 mg/kg) improved lung tissue injury, reduced the serum level of IL-1β (P < 0.001), and the mRNA levels of MPO and SP-D in lung tissues (P < 0.05) of mice. Pachymaran (100 mg/kg) increased the protein level of lung IL-2 (P < 0.01), decreased the protein level of lung SP-D (P < 0.01), and the mRNA level of IL-1β (P < 0.001) in the lung tissues of mice. Pachymaran (200 mg/kg) increased the serum level of IL-2 (P < 0.01) and lung IL-6 of mice (P < 0.05). Pachymaran (50 and 200 mg/kg) increased the mRNA level of IL-6 in the lung tissues of mice (P < 0.05). Conclusion: While the immune function of mice was suppressed by CsA, the lung tissue was also damaged. Pachymaran can improve the immunosuppression induced by CsA and improve the lung tissue injury in immunosuppressed mice.